LaNa2: Uma ferramenta para processamento de textos naturais em língua portuguesa - Guimarães, Adolfo; Bispo, Thiago Dias; Azevedo, Arthur; Macedo, Hendrik (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Many tasks in various areas of science and society depend on interaction with the computer. The more transparent and simple the interaction, the better and faster the results will become. The gain in productivity is most evident when the tasks become more complex and the amount of data available increases exponentially. For example, amount of data produced in social networks. In these case, the manual evaluation is almost impossible. Thus, the study of techniques and applications that extract and interpret this data automatically has become an essential task in the decision making of the most diverse areas. This work aims at the extension and demonstration of LaNa2: a web platform for the collection, processing, analysis and visualization of textual contents in a clear and objective way. The main differential in comparison with other tools is its free access, in addition to the adoption of Machine Learning models for textual classification. We compare LaNa2 with other tools available in the market and run experiments to demonstrate their functionality.